Evolution of the nutritional quality of packaged food supply in low- and middle-income countries following the implementation of a front-of-pack labeling scheme - Tassy, Marie; Rytz, Andreas; Eldridge, Alison L.; Mak, Tsz Ning; Hayford, Frank Ekow Atta; Feskens, Edith J. M. (Frontiers in Nutrition, 2025)
IntroductionAs packaged foods consumption increases in low- and middle-income countries (LMICs), certain governments have introduced front-of-pack labeling (FOPL) schemes to promote healthier food choices. This study assesses the evolution and nutritional quality of packaged foods in LMICs from 2015 to 2023 and examines trends in countries where FOPLs have been implemented.MethodsOn-pack information from products in the top 20 packaged food categories was retrieved from the Mintel Global New Product Database (2015–2023) in 19 LMICs. The number of new products introduced and median content of energy, sugars, sodium, saturated fatty acids (SFA), protein, and fiber were analyzed by product category, country, region and type of FOPL implemented. Evolution of the percentage of products with an improved nutritional content was compared from 2015–2017 to 2021–2023.ResultsOur findings indicate that from 2015 to 2023, the percentage of packaged meat and coffee products increased in LMICs, while more indulgent products such as cookies declined. The nutritional quality of products improved, particularly toward a reduction in total sugars and an increase in protein content. The implementation of FOPL was associated with further reductions in total sugars, and, depending on the type of scheme implemented, with reduction in sodium.DiscussionThese findings offer insights on the food environment in LMICs undergoing a nutrition transition, and on how certain food policies can be associated with reformulation of packaged foods in those countries.